Decolonizing Palestine : Hamas between the anticolonial and the postcolonial - Sen, Somdeep (Cornell University Press, 2020)
"This book considers the Palestinian struggle for liberation as it examines the two seemingly contradictory, yet coexistent anticolonial and postcolonial modes of politics adopted by Hamas following its unexpected victory in the 2006 Palestinian Legislative Council election"--